2023
DOI: 10.1186/s13717-023-00417-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere fungal community assembly varied across functional guilds in a temperate forest

Abstract: Background Rhizosphere fungi play an important role in plant community dynamics and biogeochemical cycling. While the drivers of fungal community assembly have been studied in varied ecosystems, it is still unclear how these processes function for rhizosphere soil fungi in temperate forests. Furthermore, it is unknown whether the relative contributions of important determinants remain consistent or vary across fungal ecological guilds. This study used high-throughput next-generation sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…Namely, strong spatial structure captured at the shortest spatial distances was present in ECM fungi and saprotrophs but not in yeasts; therefore, it likely captured the mycelial growth of the large, filamentous fungal species, which have been demonstrated to grow up to several metres long (Cairney, 2005). The vegetation effect observed at intermediate scales in our study corresponds with the results of other studies conducted at similar scales, where vegetation has been shown to affect fungal communities (Bahram et al., 2013; Liang et al., 2023; Odriozola et al., 2020, 2021; Peay et al., 2013; Tedersoo et al., 2020; Urbanová et al., 2015). In contrast to our hypothesis, the distribution of ECM fungi did not show stronger coupling with vegetation than the distribution of saprotrophs and yeasts.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Namely, strong spatial structure captured at the shortest spatial distances was present in ECM fungi and saprotrophs but not in yeasts; therefore, it likely captured the mycelial growth of the large, filamentous fungal species, which have been demonstrated to grow up to several metres long (Cairney, 2005). The vegetation effect observed at intermediate scales in our study corresponds with the results of other studies conducted at similar scales, where vegetation has been shown to affect fungal communities (Bahram et al., 2013; Liang et al., 2023; Odriozola et al., 2020, 2021; Peay et al., 2013; Tedersoo et al., 2020; Urbanová et al., 2015). In contrast to our hypothesis, the distribution of ECM fungi did not show stronger coupling with vegetation than the distribution of saprotrophs and yeasts.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, Liang et al. (2023) reported strong vegetation effects on ECM fungal composition when analysing samples dominated by host trees with mixed mycorrhizal types, but soil variables were the main predictors when analysing only the samples dominated by ECM‐associated trees. All samples in our study were dominated by ECM‐associated trees, which might have contributed to the weaker vegetation effects on ECM fungi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we found that fine‐root diameter, fine‐root nitrogen and phosphorus concentration, and RTD variously regulated the community structure of soil patho‐, sapro‐ and symbiotrophic fungi, supporting our third hypothesis. Generally, soil patho‐ and symbiotrophic fungi are part of the biotrophic guilds that depend on living plants to survive, while soil saprotrophicic fungi are non‐biotrophic, meaning they acquire all their nutrients from non‐living plant material or surrounding soil organic matter (Liang et al., 2023). Due to their ecological and functional dissimilarities, these fungal guild communities of biotrophic and non‐biotrophic guilds might be shaped by different determinants associating soil and plant traits (Nguyen, Williams, et al., 2016; T. Yang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%